(untitled) (Ogigia. Revista Electrónica de Estudios Hispánicos, 2020)
In this research work, the minifictional production written by Peruvians from the year 2000 is collected, since since the new millennium this textual modality has been becoming more important in Peruvian literature. Therefore, it is appropriate to present the basis for the start of a major study on the short story written by Peruvians.